Strategi pengembangan wisata pantai dalam upaya meningkatkan ekonomi masyarakat sekitar - Saifuddin, Saifuddin; Sulistiyani, Titin (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study seeks to find out and analyze tourism conditions, the development of Bletok beach tourism strategies in an effort to improve the economy of the surrounding community carried out by the Village Government, POKDARWIS, POKMAS, BUMDES, and the community. what supports and hinders the development of Bletok beach tourism in Bletok Village, Bungatan District, Situbondo Regency. However, the tourism sector still has several obstacles so that it is necessary to develop a tourism strategy by the village government on the economy of the surrounding community. To find out the strategy for developing Bletok beach tourism in an effort to improve the economy of the surrounding community, in this study, researchers used a qualitative research method, a case study type. Based on the results of the study that there are strategies carried out by the Village Head in the development of coastal tourism in an effort to improve the economy of the surrounding community, among others, the existence of infrastructure development, maintenance of facilities, and improvement of the community's economy. However, in implementing this strategy, there are supporting and inhibiting factors that arise both internally and externally